2018
DOI: 10.4103/jomfp.jomfp_197_16
|View full text |Cite
|
Sign up to set email alerts
|

Palatoscopy and odontometrics for sex identification and hereditary pattern analysis in a Navi Mumbai population: A cross-sectional study

Abstract: Background:Identification of an individual is a challenging task in the field of forensic odontology. Sometimes, the identity of individuals by fingerprints is difficult; hence, the examination of palatal rugae and the human dentition is a viable option.Aims and Objectives:The objective of the present study was to determine the sex of an individual and the hereditary pattern using three parameters are as follows: palatine rugae, dimensions of maxillary molar and maxillary canine.Materials and Methods:A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 21 publications
4
9
0
2
Order By: Relevance
“…9,14 The wavy pattern followed by a straight pattern was predominantly seen in females, while the curved pattern was seen most commonly in males. 11,25,26 We observed no significant differences in convergence and divergence patterns in males and females, which accords with earlier studies. 7,14 However, a previous study showed that males had more converging rugae, while females had more diverging rugae.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…9,14 The wavy pattern followed by a straight pattern was predominantly seen in females, while the curved pattern was seen most commonly in males. 11,25,26 We observed no significant differences in convergence and divergence patterns in males and females, which accords with earlier studies. 7,14 However, a previous study showed that males had more converging rugae, while females had more diverging rugae.…”
Section: Discussionsupporting
confidence: 92%
“…7,14 However, a previous study showed that males had more converging rugae, while females had more diverging rugae. 11,26 It was also seen that males had more forwardly directed rugae than females, similar to an earlier report. 12 Pereira et al 11 reported that both forward and backward were common in males, while perpendicular patterns were common in females, while Dwivedi and Nagarajappa reported that backwardly directed rugae were common in males.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations